Prior Work Experience and Entrepreneurship: The Careers of Young Entrepreneurs - Nicolas Gendron-Carrier (Institute of Labor Economics (IZA), 2023)
I investigate the mechanisms that drive sorting into entrepreneurship and entrepreneurial success among young individuals. I use Canadian matched owner-employeremployee data to conduct my investigation. Empirically, older entrepreneurs and entrepreneurs who have previously worked in high-wage firms tend to do better. To explain these findings, I develop a dynamic Roy model of career choice that features heterogeneous employers, human capital accumulation, and unobserved heterogeneity across individuals. Among other things, I find that prior work experience is particularly valuable for "subsistence" entrepreneurs. I use the estimated model to evaluate policies designed to promote entrepreneurship.
Keywords: J24; J31; J62; L26; 330; entrepreneurship; human capital; firm heterogeneity; career choice; dynamic Roy model; unobserved heterogeneity